2004
DOI: 10.1111/j.1524-475x.2004.04006.x
|View full text |Cite
|
Sign up to set email alerts
|

A Process for Systematically Reviewing the Literature: Providing the Research Evidence for Public Health Nursing Interventions

Abstract: The EPHPP has demonstrated the ability to adapt the most current methods of systematic literature reviews of effectiveness to questions related to public health nursing. Other positive outcomes from the process include the development of a critical mass of public health researchers and practitioners who can actively participate in the process, and the work on dissemination has been successful in attracting external funds. A program of research in this area is being developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
1,624
2
21

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,748 publications
(1,653 citation statements)
references
References 19 publications
6
1,624
2
21
Order By: Relevance
“…This tool was selected for its comprehensive ability to assess the methodological quality of non‐randomized studies and has shown good reliability and validity 21, 22. A 3‐point scale was used for the following criteria: selection bias, study design, confounders, blinding, data collection methods, and study withdrawals.…”
Section: Methodsmentioning
confidence: 99%
“…This tool was selected for its comprehensive ability to assess the methodological quality of non‐randomized studies and has shown good reliability and validity 21, 22. A 3‐point scale was used for the following criteria: selection bias, study design, confounders, blinding, data collection methods, and study withdrawals.…”
Section: Methodsmentioning
confidence: 99%
“…Risk of bias was assessed for each study using accepted tools for cross-sectional study designs (National Institutes of Health, 2014;The Joanna Briggs Institute, 2016;Thomas, Ciliska, Dobbins, & Micucci, 2004). Items were adapted to the current question using pre-decided criteria, and updated, as needed, after the two assessors (KS, MM) had independently rated and discussed the first three papers (alphabetically) until agreement was reached.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Study quality was assessed using the Effective Public Health Practice Project (EPHPP) "Quality Assessment Tool for Quantitative Studies", developed for use in public health research [45] a robust tool with appropriate psychometric properties to adequately assess quality of evidence [46]. Included studies were assessed for homogeneity and synthesis via meta-analysis ruled out due to the extreme heterogeneity in participant selection criteria, interventions e.g.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…Instead a narrative analysis was conducted as a best case alternative, able to cope with this variation [50] using methodological guidance outlined in Thomas et al [45] and reported according to the framework recommended by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement (www.prismastatement.org), providing an analysis of the relationships within and between studies and an overall assessment of the robustness of the evidence.…”
Section: Data Extraction and Analysismentioning
confidence: 99%